Concomitant vs. Staged Treatment of Varicose Tributaries as an Adjunct to Endovenous Ablation: A Systematic Review and Meta-Analysis. (September 2020) - Aherne, Thomas M.; Ryan, Éanna J.; Boland, Michael R.; McKevitt, Kevin; Hassanin, Ahmed; Tubassam, Muhammad; Tang, Tjun Y.; Walsh, Stewart
Abstract : Objective: This review compares the outcomes of both concomitant and staged superficial varicose tributary (SVT) interventions as an adjunct to endovenous truncal ablation. Methods: A systematic search of Medline through Pubmed, Embase, and the Cochrane Central Register of Controlled Trials was last performed in November 2019. All studies comparing the outcomes of both concomitant and staged treatments for SVT as an adjunct to endovenous truncal ablation were included. Each included study was subject to an evaluation of methodological quality using the Downs and Black assessment tool. Outcomes assessed included rates of re-intervention, complications, and thrombotic events. Quality of life (QOL) and disease severity were also analysed. Data were pooled with a random effects model. Results: Fifteen studies (6 915 limbs) were included for analysis. Included studies were of reasonable methodological quality. Re-intervention rates were significantly lower in the concomitant group (6.3% vs. 36.1%) when compared with staged intervention (relative risk [RR] 0.21 [95% CI 0.07–0.62], p = .004, I 2 = 90%, p ≤ .001). Reported complications (RR 1.14 [95% CI 0.67–1.93], p = .64) and rates of deep venous thrombosis (RR 1.41 [95% CI 0.72–2.77] p = .31) were similar in each group. Overall disease severity (Venous Clinical Severity Score) was lower in the concomitant group (−1.16 [95% CI, −1.97– −0.35] p = .005), while QOL, assessed using the Aberdeen Varicose Vein Questionnaire, favoured concomitant treatment when measured at less than three months (weighted mean difference [WMD] −3.6 [95% CI, −7.17– −0.03] p = .050) and between three and 12 months (WMD -1.61 [95% CI, −2.99– −0.23] p = .020). Conclusion: Concomitant and staged treatments are safe and effective. Improvements in early disease severity and QOL scores were better in the concomitant group. While meta-analysis suggests that concomitant intervention offers significantly lower rates of re-intervention, studies assessing its merits are subject to some biases. This benefit was not reflected by the randomised trial subgroup analysis, which identified no difference in re-intervention.